Analisis Kehilangan Air Irigasi di Saluran Irigasi Colo Timur - Ahmad Fahrudin; Agus Hari Wahyudi; Solichin Solichin (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2024)
The analysis of water irrigation loss is very importance, as the loss of water in irrigation canals may have a detrimental impact on the overall performance of the irrigation system. The occurrence of water loss can be attributed to a multitude of factors, including damage to the channel, evaporation, seepage, and other phenomena that diminish the usability of the water in question. Consequently, an analysis of water loss can assist in determining the quantity of water lost, as well as the factors that contribute to the occurrence of water loss. This enables the implementation of preventive and corrective measures to enhance the efficiency of water usage. The objective of this study is to ascertain the value of water loss in the secondary channel of the East Colo Irrigation Area. The research methodology entails direct field measurement of water irrigation loss. The results demonstrate that the average value of the percentage of water loss from the Geneng Secondary channel is 11.07%, with a maximum water loss percentage of 23.66% and a minimum water loss percentage of 2.84%. In the Pulosari Secondary channel, the average value of the percentage of water loss is 13.82%. In the Krikilan Secondary channel, the maximum water loss percentage was observed to be 18.38%, while the minimum is 9.36%. The average value of the percentage of water loss was found to be 22.81%, with a maximum of 26.01% and a minimum of 19.22%. The factors that cause water loss obtained an average percentage value of water loss due to evaporation of 0.22% in the Geneng Secondary channel, 0.04% in the Pulosari Secondary channel, and 0.01% in the Krikilan Secondary channel. For the average percentage value of water loss due to seepage of 0.001% in the Geneng Secondary channel, 0.0001% in the Pulosari Secondary channel and Krikilan Secondary channel.